THE MARITIME CULTURAL VALUES OF THE BIDAR BOAT ON THE MUSI RIVER - Nur Syafarudin, - (Departemen Psikologi Pendidikan dan Bimbingan, Universitas Pendidikan Indonesia (UPI), 2023)
Indonesia has a variety of cultures that are preserved by the community in relation to its natural environment. Bidar boats are one of the maritime cultural heritages that are still preserved in Palembang today. The problem in this research is what are the maritime cultural values of the bidar boat on the Musi River. The purpose of this study was to determine the maritime cultural values of the bidar boat on the Musi River. The research method used is qualitative, it is used to reveal the culture in the tradition of the bidar boat on the Musi River which is carried out by the community from generation to generation. The location of the research was conducted in Palembang City, South Sumatra, to be precise on the Musi River. Data collection techniques were in the form of observation, documentation and interviews. The results of the identification of bidar boats on the Musi River could be concluded that the bidar boats on the Musi River have maritime cultural values, namely knowledge, skills, cooperation, courage, hard work, honesty, responsibility and identity